Mitochondria-targeting polydopamine-coated nanodrugs for effective photothermal- and chemo-synergistic therapies against lung cancer. (1st August 2022) - Meng, Ziyu; Wang, Binchao; Liu, Yiqiang; Wan, Yejian; Liu, Qianshi; Xu, Huasheng; Liang, Renchuan; Shi, Ying; Tu, Peng; Wu, Hong; Xu, Chuan
Abstract: Targeting mitochondria via nano platform emerged as an attractive anti-tumor pathway due to the central regulation role in cellar apoptosis and drug resistance. Here, a mitochondria-targeting nanoparticle (TOS-PDA-PEG-TPP) was designed to precisely deliver polydopamine (PDA) as the photothermal agent and alpha-tocopherol succinate (α-TOS) as the chemotherapeutic drug to the mitochondria of the tumor cells, which inhibits the tumor growth through chemo- and photothermal- synergistic therapies. TOS-PDA-PEG-TPP was constructed by coating PDA on the surface of TOS NPs self-assembled by α-TOS, followed by grafting PEG and triphenylphosphonium (TPP) on their surface to prolong the blood circulation time and target delivery of TOS and PDA to the mitochondria of tumor cells. In vitro studies showed that TOS-PDA-PEG-TPP could be efficiently internalized by tumor cells and accumulated at mitochondria, resulting in cellular apoptosis and synergistic inhibition of tumor cell proliferation. In vivo studies demonstrated that TOS-PDA-PEG-TPP could be efficiently localized at tumor sites and significantly restrain the tumor growth under NIR irradiation without apparent toxicity or deleterious effects. Conclusively, the combination strategy adopted for functional nanodrugs construction aimed at target-delivering therapeutic agents with different action mechanisms to the same intracellular organelles can be extended to other nanodrugs-dependent therapeutic systems. Graphical Abstract: